Isobutrin from butea monosperma (flame of the forest): a promising new natural sensitizer belonging to chalcone class - Agarkar, Shruti A.; Kulkarni, Roshan R.; Dhas, Vivek V.; Chinchansure, Ashish A.; Hazra, Partha; Joshi, Swati P.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2011)
In this work, ``isobutrin'', an ecofriendly sensitizer that is extracted from Butea monosperma (commonly known as ``Flame of the Forest'') flowers, is introduced. It is a bright yellow pigment belonging to the chalcone class and is examined as a sensitizer for optoelectronic applications. It is observed that chelation of this dye with Ti ions results into a strong dye-TiO(2) charge transfer (DTCT) band in the visible region. This Ti-Isobutrin chelate is stable, irreversible and its formation is studied using Benesi-Hildebrand plot. The locations of HOMO-LUMO states of the Ti-isobutrin chelate and the corresponding band alignment with TiO(2) are obtained. Also, a thermal stability test revealed that isobutrin is stable above 100 degrees C.
Keywords: Butea monosperma; chalcone; dye-sensitized solar cell; isobutrin; sensitizer; TiO(2)

Antimycobacterium activity of coumarins from fruit pulp of aegle marmelos (L.) correa - Chinchansure, Ashish A.; Shamnani, Neelam; Arkile, Manisha A.; Sarkar, Dhiman; Joshi, Swati P. (International Journal of Basic and Applied Chemical Sciences, 2015)
Phytochemical investigation of n-butanol fraction of acetone extract of Aegle marmelos fruit has afforded four compounds coumarins marmelosin (1), marmin (2) and xanthotoxol (3) and flavonoid kaempferol 3- O-rhamnoside, afzelin (4). All the isolated compounds were evaluated for their antimycobacterium activity against Mycobacterium tuberculosis H37Ra and Mycobacterium bovis. Compounds 1 and 2 exhibited antimycobacterium activity against M. tuberculosis H37Ra with an IC50 12.46 µg/mL and 4.31 µg/mL respectively whereas, at 100 µg/mL, 62.5% and 82.4% growth inhibition of M. bovis was observed respectively. Compounds 1 and 2 were also evaluated against two gram positive bacteria Staphylococcus aureus, Bacillus subtilis and one gram negative bacteria Escherichia coli. Compound 1 at 100 µg/mL, showed growth inhibition, 64.6% and 74.9% of E. coli and B. subtilis respectively.

Leucas mollissima, a source of bioactive compounds with antimalarial and antimycobacterium activities - Chinchansure, Ashish A.; Arkile, Manisha A.; Shukla, Anurag; Shanmugam, Dhanasekaran; Sarkar, Dhiman; Joshi, Swati P. (Planta Medica Letter, 2015)
A phytochemical investigation of the acetone extract from the aerial parts of Leucas mollissima afforded one new (−)epi-marmelo lactone, (2 S, 4R, 6 S)-2,6-dimethyl-6 hydroxy-7-ene-4-olide (1), along with five known compounds, schensianol A (2), vanillin (3), β-hydroxy propiovanillone (4), lanost-9(11),25-diene-3β,24β-diol (5), and lanost-9(11),23E(24)-diene-3β,25-diol (6). Similarly, an investigation of the methanol extract of the aerial parts of L. mollissima resulted in the isolation of three known compounds, (+)-syringaresinol (7), anisofolin A (8), and apigenin 7-O-β-D(− 6′′-p-E-coumaroyl)-glucoside (9). Structure elucidation of the isolated compounds was carried out using detailed analysis of 1D and 2D nuclear magnetic resonance. All compounds were evaluated for antimalarial activity against Plasmodium falciparum (3D7) and for antimycobacterium activity against Mycobacterium tuberculosis H37Ra and Mycobacterium bovis. Compound 8 was found to have promising antimalarial activity (IC50 4.39 ± 0.25 µM), promising antimycobacterium activity [IC50 4.50 ± 0.75 µM (3.31 µg/mL)] against M. tuberculosis H37Ra and at 100 µg/mL, showed 55.6 % inhibition of M. bovis. Compound 9 showed moderate inhibition of P. falciparum growth (35 % inhibition at 10 µM) with respect to the positive control atovaquone and 67.4 % inhibition against M. bovis at 100 µg/mL with respect to the positive control rifampicin.

New butenolide cinnamate and other biological active chemical constituents from Polygonum glabrum - Said, Madhukar S.; Chinchansure, Ashish A.; Nawale, Laxman; Durge, Ankita; Wadhwani, Ashish; Kulkarni, Smita S.; Sarkar, Dhiman; Joshi, Swati P. (Natural Product Research, 2015)
Phytochemical investigation of the methanol extract of the aerial parts of Polygonum glabrum afforded one new natural product (-)-2-methoxy-2-butenolide-3-cinnamate (1) along with six known compounds, -hydroxyfriedalanol (2), 3-hydroxy-5-methoxystilbene (3), (-) pinocembrin (4), sitosterol-(6-O-palmitoyl)-3-O–d-glucopyranoside (5), (-) pinocembrin-5-methyl ether (6) and sitosterol-3-O–d-glucopyranoside (7). Compound 1 showed promising in vitro anti-HIV-1 activity against primary isolates HIV-1(UG070) (X4, subtype D) and HIV-1(VB59) (R5, subtype C) assayed using TZM-bl cell line with IC50 in the range of 15.68-22.43g/mL. The extract showed TI in the range of 19.19-27.37 with IC50 in the range of 10.90-15.55g/mL. Compounds 1, 3 and 4 exhibited in vitro anti-mycobacterium activity against Mycobacterium tuberculosis H37Ra with IC50 values of 1.43, 3.33 and 1.11g/mL in dormant phase and 2.27, 3.33 and 1.21g/mL in active phase, respectively. Compound 4 was found to be the most active antiproliferative with IC50 values of 1.88-11.00g/mL against THP-1, A549, Panc-1, HeLa and MCF7 cell lines.
Keywords: anti-HIV-1; anti-mycobacterium; antiproliferative; phytochemicals; Polygonaceae; Polygonum glabrum

Recent development of plant products with anti-glycation activity: a review - Chinchansure, Ashish A.; Korwar, Arvind M.; Kulkarni, Mahesh J.; Joshi, Swati P. (RSC Advances, 2015)
Diabetes mellitus (DM) is an endocrine disorder characterized by chronic hyperglycemia, which results from an absolute or a relative deficiency of insulin or resistance to insulin. Hyperglycemia is increasingly linked to the pathogenesis of diabetic complications in individuals with long-duration diabetes. One of the inevitable consequences of hyperglycemia is the enhanced accumulation of advanced glycation end-products (AGEs), which are implicated in the pathogenesis of diabetes. Various natural products and their active constituents have reportedly been used for the treatment of diabetes and its complications. Some of these molecules are known to have anti-glycation activity. The search for novel anti-glycation agents from various sources is gaining a lot of importance. Attention has especially been focused on plants with an ethnopharmacological background and also on plants rich in triterpenoids and phenolics, which generally exhibit antioxidant and anti-glycation effects. Plant extracts or compounds obtained from them that possess both antioxidant and anti-glycation activities might have great therapeutic potential for treating diabetic complications. This review highlights the anti-glycation activities of phytochemicals, which will aid in the identification of lead molecules for the development of new anti-glycation drugs.

Rottlerin derivatives and other compounds from mallotus philippinensis fruits and their potential antimycobactrial activity - Bhardwaj, Rima; Chinchansure, Ashish A.; Kulkarni, Roshan R.; Arkile, Manisha A.; Sarkar, Dhiman; Joshi, Swati P. (Planta Medica Letters, 2015)
The methanolic extract of the fruits of Mallotus philippinensis afforded 13 compounds, 7,11-diketo-lanost-3-ol (1, as acetate), lanosta-8-ene-3β-ol (2, as acetate), pregnenolone (3, as acetate), trans-chalcone (4), kamalachalcone E (5), oleanolic acid (6), gallic acid (7), kaempferol (8), myricetin (9), 1-(5,7-dihydroxy-2,2,6-trimethyl-2 H-1-benzopyran-8-yl)-3-phenyl-2-propen-1-one (10), 4′-hydroxyisorottlerin (11), rottlerin (12), and shikimic acid (13). Compound 1 was isolated as a new natural product and its structure was elucidated by 1D and 2D nuclear magnetic resonance analyses including heteronuclear single quantum correlation, heteronuclear multiple-bond correlation, correlation spectroscopy, and nuclear Overhauser effect spectroscopy experiments. All of the isolated compounds were evaluated for their antimycobacterium activity against Mycobacterium tuberculosis H37Ra. Compounds 11 and 12 exhibited promising inhibitory activity with IC50 values of 0.89 ± 0.33 µg/mL (MIC 2.06 ± 0.41 µg/mL) and 7.59 ± 0.42 µg/mL (MIC 11.56 ± 0.35 µg/mL), respectively.

New dinor-cis-labdane diterpene and flavonoids with antimycobacterium activity from colebrookea oppositifolia - Chinchansure, Ashish A.; Arkile, Manisha A.; Shinde, Dinesh R.; Sarkar, Dhiman; Joshi, Swati P. (Planta Medica Letters, 2016)
The new 14,15-dinor-cis-labdane diterpene, named (+)-14,15-dinor-9α-hydroxy-cis-labd-11(E)-en-13-one (1), was isolated from the acetone extract of the aerial parts of Colebrookea oppositifolia, along with the known compounds alnustin (2), mosloflavone (3), flindulatin (4), 5,6,7-trimethoxy baicalein (5), tanetin (6), scutellarein 4′-methyl ether (7), apigenin (8), caffeic acid (9), anisofolin A (10), apigetrin (11), and forsythoside A (12). Structures of the new and known compounds were established by detailed analysis of 1D and 2D nuclear magnetic resonance studies. The isolated compounds 1–12 were evaluated for their antimycobacterium activity against Mycobacterium tuberculosis H37Ra and Mycobacterium bovis in both dormant and active phases. Compounds 1, 7, and 8 exhibited inhibitory activity against M. tuberculosis with IC50 values in the range of 8.1–55.0 µM (MIC 14.4–119.7 µM) in the active phase and 7.4–43.5 µM (MIC 11.5–123.3 µM) in the dormant phase. Similarly 1, 7, and 8 exhibited inhibitory activity against M. bovis with IC50 values in the range of 4.1–98.5 µM (MIC 13.7–161.0 µM) in the active phase and 4.1–111.1 µM (MIC 13.0–166.4 µM) in the dormant phase.

Acetone and methanol fruit extracts of terminalia paniculata inhibit HIV-1 infection in vitro - Durge, Ankita; Jadaun, Pratiksha; Wadhwani, Ashish; Chinchansure, Ashish A.; Said, Madhukar; Thulasiram, H. V.; Joshi, Swati P.; Kulkarni, Smita S. (Natural Product Research, 2017)
In this study, we report the in vitro anti-HIV1 activity of acetone and methanol extracts of fruit of Terminalia paniculata. Cytotoxicity tests were conducted on TZM-bl cells and peripheral blood mononuclear cells (PBMC), the CC50 values of both the extracts were 260g/mL. Using TZM-bl cells, the extracts were tested for their ability to inhibit replication of two primary isolates HIV-1 (X4, Subtype D) and HIV-1 (R5, Subtype C). The activity against HIV-1 primary isolate (R5, Subtype C) was confirmed using activated PBMC and by quantification of HIV-1 p24 antigen. Both the extracts showed anti-HIV1 activity in a dose-dependent manner. The EC50 values of the acetone and methanol extracts of T. paniculata were 10.3g/mL. The enzymatic assays were performed to determine the mechanism of action which indicated that the anti-HIV1 activity might be due to inhibition of reverse transcriptase (77.7% inhibition) and protease (69.9% inhibition) enzymes.